Numerical investigation of two-phase flow through tube bundles based on the lattice Boltzmann method. Issue 1 (31st December 2022) - Cheng, Pengxin; Zhang, Jinsong; Gui, Nan; Yang, Xingtuan; Tu, Jiyuan; Jiang, Shengyao
Abstract : In pursuit of stable operation in thermal hydraulic engineering, this paper researches two-phase flow through tube bundles by the lattice Boltzmann method. The single-relaxation-time lattice Boltzmann model and the multicomponent, multiphase pseudo-potential lattice Boltzmann model are adopted. Specifically, the two-phase flow past double-tandem circular cylinders, double-parallel circular cylinders, in-line tube bundles and staggered tube bundles with various spacing ratios is investigated. The vortex variable distribution and vortex shedding law under different working conditions are further compared to obtain the time-averaged drag, oscillating drag and Strouhal number. The variation law of lift coefficient and lift power spectrum with different spacing ratios is revealed. With increasing spacing ratio, the mutual interference between the double-tandem circular cylinders is weakened, the amplitude of the time-averaged drag on the double-parallel circular cylinders is reduced and the lift power spectrum changes from a double-peak distribution to a single-peak structure. The drag and lift of the center column of in-line tube bundles are lower than those on both sides, while the oscillating drag of the odd-row columns of staggered tube bundles is higher than that of even-row columns. These results contribute toward laying a solid foundation for future research on multiphase tube bundle flow issues in nuclear engineering.